KAEDAH BACAAN RIWAYAT WARSY - Muhammad Jabir (State Institute of Islamic Studies (IAIN) Palu, 2007)
According to historical record, qira'ah al-Qur'an, had existed since the revelation of the Qur'an. Nevertheless, not until the early second century of Hijriyah did its distribution to various other parts of the Islamic world begin. The qira'ath was taught from generation to generation till the epoch of Imam of qir’ah. Majma'ul Buhus (Research Institute) of Al-Azhar, Cairo, in its congress dated 20-27th April, 1971, had decided that qira'ah al-Qur'an was tauqifiy (Devine ordain) deriving from ruwat al-mutawatirah. For this reason, the congress recommended that the Islamic states not recite the Qur'an using one kind of qira’ah only, that is riwayat hafsh version. The purpose was to preserve other qira'ah from its extinct.Kata Kunci: Riwayat warsy, qira'ah al-Qur’an, farsyul huruf